THE CHALLENGE OF TECHNOLOGICAL INNOVATION AND LINES OF RESEARCH IN ENGINEERING - Barrutia Feijóo, W. (1998)
The gap among developed and underdeveloped economies has a direct relation with their different level and approach to their research and develpoment efforts. Particularly the integration of their science and technology strategies among different parties. The study reviews technological innovation issues lo take into account by the state, industries and Universities.